(untitled) (Journal of Bangladesh Institute of Planners, 2017)
With age old practice of using bicycle in rural areas of Bangladesh, bicycle has been evolved as a transport option for urban dwellers. It has been used for recreational and non-recreational purposes, like commuting, shopping etc. This number is growing day by day. Studying cyclists’ socio-demographic and economic profile is important to identify the groups inclined to use cycle for commuting. This paper discusses about the socioeconomic characteristics and problems of office going bicycle users in Dhaka city. For this study, six commercial areas of Dhaka city (Motijheel, Old Dhaka, Gulshan-Banani, Karwan Bazar, Mohakhali and Mirpur) are selected as study area. With 95% confidence interval 300 respondents were surveyed. Cyclists are mainly from low and medium income groups with an average age 28. After 2009, the number of cyclists got drastic increase, particularly high income groups are found more interested. Safety issue, parking space scarcity and not having bicycle lane are the highest complained problems of cyclists. This study provides a ground of baseline data for future researchers as there is no previous study done on this topic. JBIP, Vol. 10, 2017 (Printed in December 2019), pp. 55-70